2007
DOI: 10.1095/biolreprod.106.057950
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Cellular and Molecular Analysis of the Effect of Progesterone Withdrawal in a Murine Model of Decidualization1

Abstract: The endometrium is a dynamic tissue that undergoes periodic growth, remodeling and breakdown under the influence of ovarian steroid hormones. To investigate the molecular mechanisms underlying these processes, we used a murine model to mimic the decidualization and regression observed in humans. Ovariectomized mice were treated sequentially with steroid hormones, and subsequently, to induce decidualization, oil was injected into the uterine lumen. The animals were then divided into progesterone-maintained and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…While uterine natural killer (uNK) cells occur in high amounts during the implantation window, there is a marked increase in numbers of local macrophages and neutrophils prior to menstruation [20]. Similarly, an increase in endometrial macrophages and neutrophils in the decidualized mouse uterus has been reported previously [21], [22]. In those studies singular markers were used for identifying cells and only few tissue sections were analyzed by immunohistochemistry, which are not necessarily representative for the whole organ.…”
Section: Discussionmentioning
confidence: 99%
“…While uterine natural killer (uNK) cells occur in high amounts during the implantation window, there is a marked increase in numbers of local macrophages and neutrophils prior to menstruation [20]. Similarly, an increase in endometrial macrophages and neutrophils in the decidualized mouse uterus has been reported previously [21], [22]. In those studies singular markers were used for identifying cells and only few tissue sections were analyzed by immunohistochemistry, which are not necessarily representative for the whole organ.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the production of new B-lineage precursor lymphocytes in murine bone marrow was suppressed by 20-30% after exposure to estrogen, which might explain the difference in muscle IGL [94]. Progesterone has been also shown to affect the expression of IGL mRNA in murine endometrium [95]. In contrast others reported increased levels of IgM, IgG, and IgA immunoglobulins in female rats, and demonstrated androgen interference with maturation processes of B-cells [92,93].…”
Section: Sexually Dimorphic Proteinsmentioning
confidence: 99%
“…Furthermore, macrophages have also been associated with glandular cell loss [12] and regulation of angiogenesis [50] during the menstrual phase. A tissue xenograft model of menstruation, developed by Cheng et al [62], has also shown that immune-related genes, including those known to be expressed by macrophages, are tightly regulated in response to progesterone withdrawal.…”
Section: The Endometrial Macrophagementioning
confidence: 99%